1984
DOI: 10.1111/j.1365-2621.1984.tb12431.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Chlorine Dioxide for Controlling Microorganisms During the Handling and Storage of Fresh Cucumbers

Abstract: Chlorine dioxide (ClOz) was very effective in killing microorganisms in waters used for handling cucumbers. It was at least 10 times more effective than chlorine or acidified solutions of stabilized chlorine dioxide (Anthium Dioxcide, International Chemicals, Clark, NJ). Model systems indicated that feeding rates of 20-35 ppm/hr were adequate to maintain effective and detectable residues of Cl02 in both washing and hydrocooler waters. However, holding cucumbers in water with even high concentrations (100 ppm) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 12 publications
0
21
1
Order By: Relevance
“…Similar findings were reported by Patterson (1968Patterson ( , 1969 and Dougherty (1974) in washing sheep, beef, and broiler carcasses with 20 ppm chlorinated water and 8 ppm ClO 2 solution, respectively. Surface microbial populations on cucumbers changed only slightly after dipping in 105 ppm ClO 2 solution for 15 min (Costilow et al, 1984). Our study showed that some chlorinating solutions, even at 400 ppm, did not completely kill L. monocytogenes added onto fish cubes.…”
Section: Bactericidal Efficiency On Listeria Added To Fish Cubescontrasting
confidence: 47%
See 1 more Smart Citation
“…Similar findings were reported by Patterson (1968Patterson ( , 1969 and Dougherty (1974) in washing sheep, beef, and broiler carcasses with 20 ppm chlorinated water and 8 ppm ClO 2 solution, respectively. Surface microbial populations on cucumbers changed only slightly after dipping in 105 ppm ClO 2 solution for 15 min (Costilow et al, 1984). Our study showed that some chlorinating solutions, even at 400 ppm, did not completely kill L. monocytogenes added onto fish cubes.…”
Section: Bactericidal Efficiency On Listeria Added To Fish Cubescontrasting
confidence: 47%
“…ClO 2 was seven times more potent than aqueous chlorine in killing bacteria in poultry processing chill water (Lillard, 1979). Bactericidal activity of ClO 2 was not affected by alkaline conditions, such as the pH 6-10 of most food processing operations, and/or the presence of high levels of organic matter (Costilow et al, 1984;White, 1972). Therefore, ClO 2 maintains bactericidal activity far longer than chlorine.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorine dioxide (ClO 2 ) gas for example, has been extensively studied for its proven efficacy as a potent sanitizer and disinfectant capable of reducing populations of pathogenic microorganisms that compromise food safety (AbdulRaouf, Beuchat, & Ammar, 1993;Benarde, Snow, & Olivieri, 1967;Costilow, Uebersax, & Ward, 1984;Du, Han, & Linton, 2002;Han, Sherman, Linton, Nielsen, & Nelson, 2000;Netramai, 2011;Reina, Fleming, & E.G. Humphries, 1998;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…The soaking of cucumbers in a 25‐ppm ClO 2 wash water for 15 min caused a 5 log reduction of total bacteria, while the soaking in a chlorine solution of the same concentration reduced the bacterial numbers by less than 10‐fold. However, a treatment with 105 ppm ClO 2 for 15 min was needed to completely remove the microbial population on the surface of fresh cucumbers (Costilow and others 1984; Reina and others 1995). The significant differences of bactericidal effect between the washing water and food by treatment of the ClO 2 solution are due to the fact that microorganisms are able to adhere and colonize on the surfaces of food to form complex, structured layers known as biofilms (Carpentier and Cerf 1993).…”
Section: Introductionmentioning
confidence: 99%